PENGGUNAAN GAYA BAHASA HIPERBOLA DAN PEMBELAJARAN MONETISASI FACEBOOK - Ammah, Erisy Syawiril (INCARE, International Journal of Educational Resources, 2022)
This paper analyzes how the use of hyperbole on social media facebook. This style of language when processed in such a way can be a powerful thing to attract or influence people, make video posts and descriptions, or write statuses on Facebook. Also discussed about facebook monetization learning by utilizing the page (fanspage) by displaying sample images and steps. Facebook monetization is now being used by many people as a source of income. It turns out that the use of hyperbole has a very big influence on Facebook monetization, this is because the more crowded and viral the videos are posted, of course, the more income they get. This paper also shows examples of interrelated facebook monetization steps to support each other.